2020
DOI: 10.1111/jdv.16202
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world data from a single Greek centre on the use of secukinumab in plaque psoriasis: effectiveness, safety, drug survival, and identification of patients that sustain optimal response

Abstract: Background Few studies have investigated the long-term outcomes of secukinumab in real-life psoriasis treatment where diverse patient profiles require a personalized approach. Objectives To determine long-term performance of secukinumab in moderate-to-severe plaque psoriasis, and identify potential clinical factors predictive of sustained optimal response under real-world conditions. Methods In this 78-week, single-centre, retrospective study, effectiveness, safety and drug survival of secukinumab were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 25 publications
(88 reference statements)
8
23
3
Order By: Relevance
“…It has been reported that patients with BMI ≥30 had a lower response to secukinumab. [ 11 , 12 ] However, this was not seen in our study. In some studies, age and comorbidities were believed to affect the bioavailability and biotherapeutics of biological medications.…”
Section: Discussioncontrasting
confidence: 83%
“…It has been reported that patients with BMI ≥30 had a lower response to secukinumab. [ 11 , 12 ] However, this was not seen in our study. In some studies, age and comorbidities were believed to affect the bioavailability and biotherapeutics of biological medications.…”
Section: Discussioncontrasting
confidence: 83%
“…These results are similar or numerically slightly higher compared to the ones previously reported in real-world cohorts. 2,5,7 The percentages of patients with a PASI score of ≤1, ≤2, ≤3 and ≤5 were higher at all studied time points when compared to other studies, 8 albeit there seems to be no major differences between bio-naïve and bio-experienced patients, similar to other studies. 9 One possible reason for these similar results between groups is that the majority of bio-experienced patients (70%) was previously exposed to only one biologic, being therefore less difficult to treat than patients with two or more previous biological therapies.…”
supporting
confidence: 82%
“…Psoriasis is a chronic and debilitating immune-mediated inflammatory disease, associated with an increased risk for comorbidities and a substantial psychologic and socioeconomic impact that can last a lifetime, 1,2 for which secukinumab has demonstrated high efficacy and a very favorable safety profile in several real-world studies. [3][4][5][6] This retrospective single-center cohort study collected data from 66 patients treated with secukinumab up to 40 weeks in a real-world setting, and evaluated secukinumab drug survival, effectiveness and safety profile.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(9, 10) While rapid response and long-term effectiveness were indicated to be of high importance among patients with moderate to severe disease as well as physicians making treatment decisions, (2,11) there is evidence that current biologic treatments may lose effectiveness over time. (12), (13,14) The newer biologic therapies are those that inhibit the IL-17 or IL-23 pathways. Ixekizumab (Taltz®, IXE), an IL-17 antagonist, was approved in the US on March 22, 2016 for the treatment of adults with moderate-to-severe plaque psoriasis who are candidates for systemic therapy or phototherapy.…”
Section: Introductionmentioning
confidence: 99%